Infrared Drying of Seeds in a Fluidized Bed - Ya. P. Lobachevsky; S. A. Pavlov (Сельскохозяйственные машины и технологии, 2018)
Infrared drying (IR) has found wide application mainly in the food industry. Seeds of cereal crops are dried mainly by a convection method using shaft, column and bunker dryers. Such drying methods are ineffective, they are characterized by low productivity and high specific heat costs. The author has studied some methods of drying ensuring high intensity of the process with the maximum preservation of the quality of seeds. One of them is combined infrared drying. Combined modes of IR drying have a number of advantages over convection drying - quick heating of the particles ensures shortened process time, and the combination of diffusion and thermal diffusion processes facilitates the transfer of moisture from the grain mass center to the periphery, which reduces the specific heat consumption of a drying process. The author has considered a combined method with the use of a fluidized bed with a low intensity of the IR flow, with an additional supply of heat by the heated external air. (Research purpose) To develop a mathematical model of convective radiation IR drying of seeds, to calculate the surface temperature, the power of an IR-emitter, and the parameters of air heating. (Materials and methods) The parameters of combined IR drying have been determined using the regularities characteristic for convective drying, but with an equivalent heat transfer coefficient. The temperature and power of the IR energy source have been determined on the basis of permissible heat supply. The author has experimentally evaluated the efficiency of IR drying with blowing by external and heated air with convection drying. (Results and discussion) The surface temperature and the power of an IR emitter depend on the thickness of the layer, physical- and mechanical and radiological properties of seeds, permissible heat content and heat spent on the evaporation of moisture. It has been established that the exposure of combined drying is 12 percent lower than that of convective drying due to the process intensification with full preservation of the quality parameters of seeds. (Conclusions) The surface temperature and power of an IR emitter have been calculated as a function of the layer height, physical-and-mechanical and radiological properties of seeds, permissible heat content and heat spent on the evaporation of moisture. The degree of air heating with combined IR drying is proportional to the power deficit of an IR emitter and is inversely proportional to the equivalent heat transfer coefficient.